Kewenangan Ombudsman RI pada Aspek Pelayanan Publik - Ariani Zega; Lenny Husna (Jurnal Hukum Lex Generalis, 2025)
The Ombudsman of the Republic of Indonesia (ORI) is an independent state institution that plays a crucial role in overseeing the implementation of public services, particularly in addressing maladministration practices. This study aims to analyze the authority of the Ombudsman based on laws and regulations, the resolution of public service disputes, and efforts to improve its performance effectiveness. The method used is normative legal research with a statutory approach. The results show that although the Ombudsman has broad authority to receive reports, conduct investigations, and issue recommendations, its effectiveness is still hampered by the non-binding nature of recommendations, limited resources, and low agency compliance. Therefore, strengthening regulations, institutional capacity, utilization of technology, and increased public participation are needed.